Histopathological analysis of breast lump in an urban community hospital laboratory - Baral, Reetu (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Breast lump is mostly benign in nature however carcinoma of the breast also presents as a simple lump. Since breast carcinoma is the second most common killer of the female cancer it is important to detect it at early stage and treat. The purpose of the study was to analyse histopathology profile of breast lump. Methods: Histopathology samples were received, processed, reported and recorded in the Pathology laboratory of Helping Hands Community Hospital, Kathmandu. Data analysed from 2008 to 2011. Descriptive statistics was used to analyse the data. Results: Out of 1991 histopathology samples 68 were breast lumps. Fifty (73.5%) were benign and 18 (26.5%) were malignant. Ten (55.5%) of carcinoma was seen in between 41 and 50 years. Eleven (46%) of the malignant neoplasm were of Stage IIIA. Conclusions: Every fourth sample had carcinoma and it is mostly seen after 40 years of age.